Avifauna de la Reserva de la Biosfera "Montes Azules", Selva Lacandona, Chiapas, México - González García, Fernando (Instituto de Ecología, A.C., 1993)
This paper presents the resulte of ornithological observations made in vanous parte of the "Montas Azules" Biosphere Reserve in the State of Chiapas, Mexico, in a total of 950 hours of übservations in 94 days dunng 1 983-1 986. The total list contains 344 species of birds, of which 295 were observad by me, including 69 new records for the zone. A total of 53 species are migrants, 15 are transient migrants, and 5 are intertropical migrants species; the remain species are considered residente, Thirty percent of the species are apparently rectricted to primary vegetation, 40% were observad in tail second growth vegetation and 12% were recordad on the forest bordar. At least 13 species are classified as threatened or in danger of extinction, but 36 species can be hervested with reasonable Controls. Three of the migratory species are new records for the State of Chiapas and another tour species are new records for Mexico. Forty nine of the species heve been classified as uncommon, 29% as common, 14% as abundant, 5% as occasional, and 3% as rare. Fitly two percent are insectivores, 17% are frugivores, 11 % carnivores, 9% are granívoras and 7% are nectarivores, The familias with the greatest number of species are Emberizidae (82), Tyrannidae (38), Accipitndae (23), Trochilidae (19), Ardeidae and Columbidae (11). The general ecológical data of each species are included in a coinmented list of especies. 11 is obvious that longer period of observations and collecting are necessary for understanding our birds, and that longer term studies are necessary for establishmg strategies for protecting and conserving both the fauna and their hábitat.